English spinet with particular reference to the schools of Keene and Hitchcock - Mole, Peter Geoffrey (The University of Edinburgh, 2009)
Organological inspections of a representative sample of English spinets made during the period 1680-1740 have been performed. The sample includes instruments made by Stephen Keene and his co-workers, by the Hitchcock family firm, and by selected other makers. Analysis of the Keene instruments allows them to be classified into four groups reflecting their development in size and compass over time. In contrast, little development is discernible in spinets from the Hitchcock workshop: rather, the instruments can be seen to have existed as two basic models – a mitred tail model and a serpentine tail one. Some variations and hybrids are recognisable in both models. The commonly held view that the spinet was merely a cheap and compact substitute for the harpsichord, even during the late-Stuart and early-Georgian period, is refuted by reference to archival and iconographic evidence of the status in society of those who bought the instruments.
The English spinet with particular reference to the schools of Keene and Hitchcock
Keywords: Organology; Spinet; Harpsichord; Georgian